Ecologia e distribuição espacial de orquídeas terrícolas em Floresta Estacional Semidecidual do município de Araras, São Paulo, Brasil - Rahal, Monise Helena; De Souza-Leal, Thiago [UNESP]; Pedroso-De-Moraes, Cristiano (My University, 2015)
Our study aimed to survey and determine the floristic and spatial patterns of terricolous orchid distribution, observing how the population is influenced by microclimate in a Seasonal Semideciduous riverine forest fragment from Montevideo Farm, situated in the municipality of Araras, São Paulo, Brazil. Twenty contiguous plots of 20 x 10 m2 were defined, in which the abiotic data for our study on terricolous Orchidaceae diversity and population ecology was obtained. Seven species were identified, totaling a community sample of 711 individuals. The relative air humidity and light intensity were the environmental factors that most influenced the species distribution along the second linear correlation plots. The results show aggregated distribution patterns for all species that are part of the community. According to the data on floristic similarity, the number of species found is high in proportion to the size of the studied fragment.
Ecology and spatial distribution of terricolous orchids in a Seasonal Semidecidual Forest of Araras, São Paulo, Brazil
Keywords: Atlantic Forest; Orchidaceae; Orchidology